2014
DOI: 10.1038/srep06394
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression signature-based approach reveals the mechanisms of action of the Chinese herbal medicine berberine

Abstract: Berberine (BBR), a traditional Chinese herbal medicine, was shown to display anticancer activity. In this study, we attempted to provide a global view of the molecular pathways associated with its anticancer effect through a gene expression-based chemical approach. BBR-induced differentially expressed genes obtained from the Gene Expression Omnibus (GEO) at the National Center for Biotechnology Information (NCBI) were analyzed using the Connectivity Map (CMAP) database to compare similarities of gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Our results showed that berberine treatment inhibited the phosphorylation of Akt and mTOR, as well as mTOR downstream target p70S6K, but enhanced the phosphorylation of AMPK. A previous study reported that, in breast cells, berberine transiently activated AMPK and inhibited AKT, but did not inhibit mTOR activity[22]. Our results showed that treatment with berberine induced sustained alterations (6-24 h) of increased levels of AKT and mTOR phosphorylation in KYSE-70 cells or increased level of AMPK phosphorylation in KYSE-70 cells.…”
Section: Discussionsupporting
confidence: 55%
“…Our results showed that berberine treatment inhibited the phosphorylation of Akt and mTOR, as well as mTOR downstream target p70S6K, but enhanced the phosphorylation of AMPK. A previous study reported that, in breast cells, berberine transiently activated AMPK and inhibited AKT, but did not inhibit mTOR activity[22]. Our results showed that treatment with berberine induced sustained alterations (6-24 h) of increased levels of AKT and mTOR phosphorylation in KYSE-70 cells or increased level of AMPK phosphorylation in KYSE-70 cells.…”
Section: Discussionsupporting
confidence: 55%
“…It has been used in Ayurvedic and Chinese medicines for hundreds of years and shows a wide range of pharmacological and biochemical effects [1][2][3]. This alkaloid has a definite potential to be used as drug in a wide spectrum of clinical applications because it is effective against hyperlipidemia, diabetes, metabolic syndrome, polycystic ovary syndrome, obesity, fatty liver disease, coronary artery disease, gastroenteritis, diarrhea, hypertension, neurodegeneration, and cancer [1][2][3]. Of note, the structure of BBR makes it an attractive natural lead compound for the introduction of various chemical modifications in appropriate positions of the skeleton [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the EMT-related genes were inhibited by berberine, high BMP7, NODAL and Snail1 gene expressions of metastatic prostate cancer tissues were associated with shorter survival of prostate cancer patients and provide potential therapeutic interventions. Our another recent study reveal novel anti-migratory function of berberine in breast cancer cells through increased acetylation of -tubulin to inhibit breast cancer cells migration [26] . In conclusion, berberine may represent a promising therapy for various cancers, potentially in the prevention the migration and invasion of cancer cells through inhibiting EMT-related genes.…”
Section: Research Highlightmentioning
confidence: 81%